Effect of opened and closed questions on verbal correspondence in a card game (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
It was investigated the influence of opened (PA) and closed (PF) questions on verbal correspondence in a card game in which distorting reports increased the chances of winning. Six participants played two matches in PA and two in PF. In addition to reporting the value of the card drawn each round, they should report whether they had a card (i.e. trump card) described by the experimenter (PF) or merely describe their card (PA). Whoever reported owning or describing the trump card would win the round. Reports were checked and distortions were punished in 17% of the rounds determined by a virtual dice. Five participants presented distorted reports about the trump card and they did it more often in PF, giving evidence of the influence of the question type on verbal correspondence. Although the results point to a higher frequency of distortions in PF matches, these still need to be replicated in natural situations.
Keywords: verbal behavior; verbal correspondence; opened questions; closed questions; cards game